In vivo Two-Photon Imaging of Anesthesia-Specific Alterations in Microglial Surveillance and Photodamage-Directed Motility in Mouse Cortex - Sun, Weilun; Suzuki, Kunimichi; Toptunov, Dmytro; Stoyanov, Stoyan; Yuzaki, Michisuke; Khiroug, Leonard; Dityatev, Alexander (Frontiers in Neuroscience, 2019)
Two-photon imaging of fluorescently labelled microglia in vivo provides a direct approach to measure motility of microglial processes as a readout of microglial function that is crucial in the context of neurodegenerative diseases, as well as to understand the neuroinflammatory response to implanted substrates and brain-computer interfaces. In this longitudinal study, we quantified surveilling and photodamage-directed microglial processes motility in both acute and chronic cranial window preparations and compared the motility under isoflurane and ketamine anesthesia to awake condition in the same animal. The isoflurane anesthesia increased the length of surveilling microglial processes in both acute and chronic preparations, while ketamine increased the number of microglial branches in acute preparation only. In chronic (but not acute) preparation, the extension of microglial processes towards the laser-ablated microglial cell was faster under isoflurane (but not ketamine) anesthesia than in awake mice, indicating distinct effects of anesthetics and of preparation type. These data reveal potentiating effects of isoflurane on microglial response to damage, and provide a framework for comparison and optimal selection of experimental conditions for quantitative analysis of microglial function using two-photon microscopy in vivo.